2008
DOI: 10.1111/j.1557-9263.2008.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Density and habitat associations of Henslow's Sparrows wintering in saline soil barrens in southern Arkansas

Abstract: Although the habitat requirements of breeding populations of Henslow's Sparrow (Ammodramus henslowii) have been examined, less is known about their habitat requirements and ecology during the nonbreeding season. We estimated population densities and quantified habitat associations of Henslow's Sparrows wintering in saline soil barrens in southern Arkansas. Densities of Henslow's Sparrows in the saline soil barrens were similar to those in the Longleaf Pine (Pinus palustris) Ecosystem of the southeastern United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…2007). Holimon et al (2008) indicated that saline soil barrens in southeastern Arkansas supported Henslow's Sparrows for longer time periods post-disturbance than longleaf pine savanna habitats. Densities found on the saline barrens were similar to those found in longleaf pine savannas in the southeastern U.S. Further research is needed to assess the importance of alternative habitats for wintering Henslow's Sparrows (Cooper 2007).…”
Section: Wintering Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…2007). Holimon et al (2008) indicated that saline soil barrens in southeastern Arkansas supported Henslow's Sparrows for longer time periods post-disturbance than longleaf pine savanna habitats. Densities found on the saline barrens were similar to those found in longleaf pine savannas in the southeastern U.S. Further research is needed to assess the importance of alternative habitats for wintering Henslow's Sparrows (Cooper 2007).…”
Section: Wintering Habitatmentioning
confidence: 99%
“…Site fidelity for wintering birds was high within a winter, but not between winters (Plentovich et al 1998, Bechtoldt andStouffer 2005). Other habitats where birds have been observed throughout the wintering range include moist, grassy areas associated with power line corridors, saline soil barrens, roadsides, and unmowed fields (Pruitt 1996;Holimon et al 2008). Use of power line corridors in South Carolina was associated with depressions located on relatively exposed plateaus (Paul Champlin, Clemson University, pers.…”
Section: Wintering Habitatmentioning
confidence: 99%
“…Because Henslow's Sparrows occupy different habitats, multiple studies are needed to determine the best management for specific regions. For example, Holimon et al (2008) found that Henslow's Sparrows were positively associated with bare ground in saline soil barrens in Arkansas, but sparrows were negatively associated with patchy ground cover in longleaf pine savannas in Mississippi (Brooks 2010). Holimon et al (2008) also found that litter depth and plant height were not important in predicting the occurrence of Henslow's Sparrows, whereas Carrie et al (2002) and Bechtoldt and Stouffer (2005) found the opposite.…”
mentioning
confidence: 99%
“…For example, Holimon et al (2008) found that Henslow's Sparrows were positively associated with bare ground in saline soil barrens in Arkansas, but sparrows were negatively associated with patchy ground cover in longleaf pine savannas in Mississippi (Brooks 2010). Holimon et al (2008) also found that litter depth and plant height were not important in predicting the occurrence of Henslow's Sparrows, whereas Carrie et al (2002) and Bechtoldt and Stouffer (2005) found the opposite. Bechtoldt and Stouffer (2005) and Johnson (2006) found high densities of sparrows in drier upland and mesic low‐lying habitats, whereas other investigators found birds only in bogs (Plentovich et al 1999, Brooks 2010), perhaps due to differences in upland habitats, particularly differences in fire management, among studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation